The Effect of Milling Time on Microstrucutre and Hardness of the Aluminium Silicon Carbide (Al-10 wt % SiCp) Composite - Shamsul Baharin Jamaludin, Assoc. Prof. Dr.; Noor Ashiqin A.R.; Shaiful Rizam Shamsudin; Mohd Fitri Mohamad Wahid; Azmi Kamardin (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.